posted by .

It would be (3x-4)(3x-4).

Would the answer be 9x²+16?

  • Algebra -

    No, you are missing the middle term

    You need 3x(-4) + 3x(-4) = -24x

    (3x+4)(3x-4) = 9x^2 -16 This is the case where there wouldn't be a middle term.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    -3/[(5/x)+y] Can someone please tell me how one goes about simplifying this?
  2. pre algebra

    Is this how I would multiply? like if you have a whole number 3and 1/2yd multiplied by 4yd. Would I first multiply the 4x3 = 12 and 1/2?
  3. Algebra

    (x-3)/5 = (x-3)/x The x-3 is over the 5 and the other x-3 is over the x... I know to cross multiply so I would get 5(x-3)= x(x-3) But then would i just divide (x-3) by both sides?
  4. Algebra

    16. I am supposed to multiply the matrices B and C by each other B is: 7 6 2 -3 -1 8 9 5 and C: 0 8 -2 1 Would someone mind showing me how to multiply CB?
  5. Algebra

    89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, and this is the reply I got from someone: multiply both sides by 7 6x-42=-14 add 42 to each side 6x=28 x=14/3 But I don't get how this is done because to eliminate …
  6. Math

    I need some help!!! Multiply (Simplify your answer) (4x +5)(9x² +2x +7)
  7. math

    Multiply (4ã6-12ã5)(2ã6+6ã5) Would the answer be 8ã64-72ã25 I donft think I am supposed to multiply the 4 and 6 or the 2 and 6
  8. algebra 2

    I am trying to factor the expression -8y^2+28y-60 but can't get an answer that is correct. Here is an example of how the problem is supposed to be factored. If you have 21x2-77x-28 the first thing you would do is (21x )(x ). Next you …
  9. Algebra

    I have another one What is the value of 42-2(3x5+1)?
  10. MATH

    EQUATION: (NOTE: THIS IS A FRACTION) 5-(-2^3)(2)/6xsqrt9 -9x2 MY ANSWER: = 5-(-8)(2)/6x3-9x2 = 5+8(2)/18-9x2 = 5+16/18-18 = 21/0 = undefined

More Similar Questions